2018
DOI: 10.15520/ijnd.v8i08.2266
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preventive Bundle Guidelines on Reducing Iatrogenic Pressure Injuries among Critically Ill Neonates

Abstract: Background:There is an emerging awareness that acutely ill and immobilized neonates are at risk for iatrogenic pressure injury. Therefore, it is crucial for nurses to understand the physiologic indices of pressure injury development and their interventions should be based on evidence-based information to reduce neonatal morbidity and mortality while increasing quality of care in the neonatal care setting.The aim of this study was to evaluate the effectiveness of preventivebundle guidelineson reducing iatrogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
14

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 16 publications
1
1
0
14
Order By: Relevance
“…On the same line, Sabaq &Amer [29] in the study about the effect of preventive bundle guidelines on reducing iratogenic pressure injury among critically ill neonates and found that, there was a positive correlation between nurses knowledge and their compliance after bundle implementation (r=.657, P<0.001). Moreover, Riccioni et al, [30] stated that pressure ulcer prevention continues to be a hot topic in pediatric hospitals.…”
Section: Discussionmentioning
confidence: 82%
“…On the same line, Sabaq &Amer [29] in the study about the effect of preventive bundle guidelines on reducing iratogenic pressure injury among critically ill neonates and found that, there was a positive correlation between nurses knowledge and their compliance after bundle implementation (r=.657, P<0.001). Moreover, Riccioni et al, [30] stated that pressure ulcer prevention continues to be a hot topic in pediatric hospitals.…”
Section: Discussionmentioning
confidence: 82%
“…Analisis kritis terhadap 7 artikel hasil penelitian yang menjadi sampel dalam literature review ini dituangkan dalam tabel berikut Artikel penelitian yang ditelaah berjumlah tujuh, setiap penelitian menggunakan desain penelitian yang berbeda-beda, diantaranya ada 5 penelitian dengan quasi eksperimental dengan pendekatan pre-post with control [14]- [16], [18], [20] dan selebihnya menggunakan pra eksperimen [17] [19].…”
Section: Hasil Dan Pembahasanunclassified
“…Sabaq [20] melakukan penelitian dengan tujuan untuk mengetahui efek dari pencegahan dekubitus dalam menurunkan dekubitus pada neonatus kritis. Sampel sebanyak 60 anak yang dirawat di NICU dibagi menjadi dua kelompok antara lain 30 anak kelompok intervensi dan 30 anak kelompok kontrol.…”
Section: Hasil Dan Pembahasanunclassified
See 2 more Smart Citations